Prevalence of HIV and sexually transmitted infections among young women engaged in sex work aboard foreign fishing vessels in Kiribati - Tebuka Toatu; Paul White; Damian Hoy; Dennie Iniakwala; Onofre Edwin A Merrilles, Jr; Sameer Vali Gopalani (World Health Organization Regional Office for the Western Pacific, 2018)
Objective: To assess the prevalence of HIV and sexually transmitted infections (STIs) among women who board foreign fishing vessels for sex work in Kiribati. Methods: A cross-sectional study was designed to collect data on behavioural risk factors for STIs and knowledge of and attitudes towards HIV and STIs during 2007. Urine and blood samples were collected to test for HIV and select STIs. Descriptive statistics were performed for sociodemographic and behavioural characteristics, and χ2 tests were used to assess associations between potential key determinants and the presence of genital Chlamydia infection. Results: Women who boarded foreign fishing vessels for transactional sex were younger, had less education, were less likely to live with a partner and were less likely to be otherwise employed. Although no HIV infections were detected, more than half (57.5%) of the women were diagnosed with an STI. One quarter of the women tested positive for chlamydia, and 40% tested positive for mycoplasma. The presence of chlamydia was strongly associated with age at first sexual intercourse (P = 0.02) and number of sexual partners during the prior seven days (P = 0.02). Conclusion: The high rate of STIs in this population of sex workers is concerning given the potential of severe pregnancy-related and chronic health problems and the increased risk of transmission within the general population of Kiribati. We identified a specific sex worker population as a priority group for targeted public health efforts to prevent and control the spread of STIs in Kiribati.